Research on vertical air–water trans-media control of Hybrid Unmanned Aerial Underwater Vehicles based on adaptive sliding mode dynamical surface control. (16th April 2018) - Ma, Zongcheng; Feng, Jinfu; Yang, Jian
We address the problem of vertical air–water trans-media control of Hybrid Unmanned Aerial Underwater Vehicles in the presence of parameters uncertainty and disturbances. Hybrid Unmanned Aerial Underwater Vehicle suffers from huge changes of added mass, fluid drag force, and "ground effect" during crossing air–water surface, which easily lead to trans-media failure. A novel structure of Hybrid Unmanned Aerial Underwater Vehicle is built and introduced which adopts dual deck propellers including four air propellers and four water propellers. The dynamic model of trans-media process is developed for the trans-media process in condition that added mass, floatage, and drag force are linearized while linearization errors and "ground effect" are treated as disturbances. Attitude and altitude–depth controllers are designed based on Lyapunov stability theory and adaptive sliding mode dynamical surface control. The proposed controllers accomplish air, underwater, and "seamless" trans-media process integrated control without a priori boundary of disturbances, forcing the tracking errors to an arbitrarily small neighborhood of zero. Simulation results are presented to illustrate the control algorithm with good performance and robustness.